Modeling Marital Satisfaction and Parental Problem-Solving on Children’s Mental Health with the Mediating Role of Parental Emotional Support - Javid, Fateme; Bagheri , Sareh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to model marital satisfaction and parental problem-solving on children’s mental health with the mediating role of parental emotional support. Methods: The research method was descriptive-correlational and of the structural equation modeling type. The study population included all adolescent girls aged 15 to 18 years along with their parents residing in Tehran in 2024, from whom 258 adolescents and their parents were selected as the sample through convenience sampling. Data collection instruments included the Marital Satisfaction Questionnaire (EMSS, ENRICH, 1987) and the Problem-Solving Styles Questionnaire (PSS, Cassidy & Long, 1996) for parents, and the Emotional Atmosphere Questionnaire (FEA, Hilburn, 1964) and the General Health Questionnaire (GHQ, Goldberg, 1979) for adolescents. Parents responded to the Marital Satisfaction and Problem-Solving Styles Questionnaires, while adolescents responded to the Emotional Atmosphere and Mental Health Questionnaires. Findings: The results showed that the proposed model had a good fit. Findings also indicated that the direct path of marital satisfaction, parental problem-solving, and parental emotional support to children’s mental health was significant (P < 0.05), and the indirect path of marital satisfaction and parental problem-solving to children’s mental health through parental emotional support was also significant (P < 0.05). Conclusion: These findings suggest that marital satisfaction and parental problem-solving can affect children’s mental health through parental emotional support.